The clinical, hematological, and biochemical profiles of patients with complications due to Plasmodium vivax malaria: A case series - Amrita Jha; Sanjay Kumar Mandal; Ranjan Mondal; Sadhan Barman; Golam Muztaba; Krishnendu Das (Asian Journal of Medical Sciences, 2024)
Malaria, a protozoal infection caused by the six species of the genus Plasmodium, is one of the most important diseases known to humankind, with most infections caused by either of the two species – Plasmodium vivax and Plasmodium falciparum. Previously, it was held that falciparum malaria was responsible for causing severe, life-threatening disease, with vivax malaria causing mild or uncomplicated infections. In this case series, the clinical, hematological, and biochemical profiles of eight patients with features of complications due to P. vivax malaria, along with their clinical course, response to treatment, and clinical outcomes have been described. Among these, the most common clinical features were fever, headache, and myalgias. Five patients had altered mental status, two were prostrated, two were hypotensive, and one had recurrent generalized seizures. Three patients had pancytopenia, two had both anemia and thrombocytopenia, and one had evidence of disseminated intravascular coagulation. Six patients had clinical jaundice, four had elevated transaminases, and four had acute kidney injury. All cases showed excellent response to anti-malarial therapy. Hence, this case series revealed that P. vivax is capable of causing severe, life-threatening organ dysfunction akin to those seen in P. falciparum malaria and that early diagnosis and treatment initiation are associated with positive patient end outcomes.